Investigating Media and Communication Techniques for Campaigns against Malaria Infections in Cross River State, Nigeria - Iyorza, Stanislaus; Nsa, Bassey (PREDESTINASI, 2019)
There is no doubt about the surge in the cases of malaria infections and other diseases in Nigeria despite the huge investment in media and communication campaigns to reduce the spread. The objective of this paper is to assess the media and communication techniques usedin campaigns against malaria infections in Nigeria, identify the loopholes and search for possible solutions to existing challenges associated with media and communication. The study adopted the survey research design using quantitative method to elicit data from the study population. The total study or sample population was 643 respondents. The questionnaire was used to reach out to the respondents for the quantitative research. The quantitative data collected was analyzed using simple tables and percentages. Findings indicated that the media channels and communication techniques in the preventive/curative campaigns against malaria infections in Nigeria include use of limited number of media for a large population and use of scientific and sophisticated medical terms in communicating the malaria campaigns among other challenges. The study concludes and recommends that sponsors, donors and partners in the intervention of malaria spread in Nigeria should partner with communication agencies that should suggest use of multi-media approaches and correct interpretations of scientific terms in the preventive and curative malaria campaigns in Nigeria.